Thermal environment analysis in large-diameter SPB shield considering the coupling heat transfer effects of slurry heat transfer and ventilation system - Sheng Zhang; Zhitao Liu; Xiaoli Yue; Shuliang Zhou; Hongye Su; Liang Chen (Case Studies in Thermal Engineering)
Effective thermal environment management is crucial for underground construction safety. Slurry circulation and duct ventilation are the primary methods for temperature control in slurry-pressure-balanced(SPB) shield tunnels. However, current research focuses on surrounding rock or equipment heat transfer, with insufficient studies on the slurry coupling mechanism. This research uses a large SPB shield from the Shenzhen highway tunnel project as a case study. A numerical model is developed to investigate the impact of slurry circulation-ventilation coupling on tunnel air temperature, and validated through field experiments. The results show that the dual-field model accurately matches temperature distribution; a 2.9°C rise in slurry temperature leads to a 0.54°C increase in air temperature. The dual-duct ventilation system lowers the average tunnel air temperature by 1.86°C compared to a single-duct system. Opening the cutterhead replacement chamber door reduces chamber air temperature by 0.9°C, but the overall tunnel temperature increases slightly from 34.9°C to 35.3°C. The model characterizes the thermal environment in an SPB shield tunnel, offering valuable guidance for practical engineering applications.